An autonomic self-healing organogel with a photo-mediated modulus. Issue 98 (21st November 2016) - Xiong, Yubing; Chen, Zhijun; Wang, Hong; Ackermann, Lisa-Maria; Klapper, Markus; Butt, Hans-Jürgen; Wu, Si
Abstract : A new method is described for fabricating autonomic, self-healing, deformable organogels. Abstract : A new method is described for fabricating autonomic, self-healing, deformable organogels. We combined imidazolium-based poly(ionic liquid) (PIL) and azobenzene-grafted poly(carboxylic acid) (PAA-Azo) in N, N -dimethyl formamide. Further, complexing PIL with unirradiated ( trans ) or irradiated ( cis ) PAA-Azo tuned the elastic modulus of the organogel.